Analisis Survival Pada Financial Distress Menggunakan Model Cox Hazard - Jasmine Yolanda; Farida Titik Kristanti (UMSurabaya Publishing, 2020)
ABSTRACTCompanies need a system to prevent the emergence of financial distress to provide early warning if there are financial problems in the company. The research carried out aims to determine how much impact liquidity, leverage, independent commissioners, institutional ownership, managerial ownership, intellectual capital have on financial distress. The selected population is the companies included in the property, real estate, and building construction sector as well as the utility and transportation infrastructure sector for the 2009-2018 period. Purposive sampling technique is used in sampling by obtaining 56 samples. The analysis technique uses survival analysis with Cox Proportional Hazard model. Based on the results of data processing leverage and intellectual capital have a significant impact on financial distress.Keywords : Corporate Governance; Financial Distress; Financial Ratios; Intellectual Capital. ABSTRAK Perusahaan memerlukan sistem untuk mengantisipasi timbulnya financial distress guna memberikan peringatan dini apabila ada masalah keuangan pada perusahaan. Riset yang dilakukan tujuannya adalah mengetahui seberapa besar dampak likuiditas, leverage, komisaris independen, kepemilikan institusional, manajerial, intellectual capital terhadap financial distress. Populasi yang dipilih yakni perusahaan yang termasuk ke dalam bidang properti, real estate, dan konstruksi serta infrastruktur utilitas dan transportasi periode 2009-2018. Pengambilan sampelnya memakai teknik purposive sampling dan memperoleh 56 sampel. Teknik analisisnya memakai analisis survival dengan model Cox Proportional Hazard. Berdasarkan hasil pengolahan data leverage dan intellectual capital mempunyai dampak yang signifikan pada financial distress. Kata kunci : corporate governance; financial distress; intellectual capital; kinerja keuangan